What you can do after graduation / Priestly Lanting Layang ... [et al.] - Layang, Priestly Lanting; Abang Shamsudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
Explore the best things to do after graduation to help you make plans now that your studies are finished. After graduating from university, you have several good opportunities for your next chapter. Explore the best things to do after graduation to help you make plans now that your studies are finished. After graduating from university, you have several good opportunities for your next chapter.